2016
DOI: 10.5216/rpt.v45i4.44639
|View full text |Cite
|
Sign up to set email alerts
|

NATURAL INFECTION BY Cryptosporidium SPP. IN PRODUCTION ANIMALS: FIRST DESCRIPTION OF SUBTYPE IIa15G2R1 IN GOAT KIDS AND PIGLETS IN BRAZIL

Abstract: A criptosporidiose é uma doença entérica grave, com manifestação clínica variada e eventual mortalidade, especialmente em animais jovens. Este estudo objetivou realizar a detecção molecular e a subtipagem de Cryptosporidium spp. em cabritos, bezerros, cordeiros, leitões epotros que compartilhem o mesmo ambiente. Amostras fecais foram coletadas diretamente do reto de 192 cabritos, 184 bezerros, 44 cordeiros, 47 leitões e 26 potros com até 12 meses de idade, machos e fêmeas, de raças diferentes, provenientes dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This study demonstrated that Cryptosporidium is present in many Brazilian states, with overall frequencies similar to or higher than in other studies around the world (Cruvinel et al, 2020;Holsback et al, 2018;Toledo et al, 2017; Coelho et al, 2016;Delafosse et al, 2015;Díaz-Lee et al, 2011). The variations in the frequencies observed between the studies may be associated with age, sample size, management practices, study design or different diagnostic techniques (Hatam-Nahavandi et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This study demonstrated that Cryptosporidium is present in many Brazilian states, with overall frequencies similar to or higher than in other studies around the world (Cruvinel et al, 2020;Holsback et al, 2018;Toledo et al, 2017; Coelho et al, 2016;Delafosse et al, 2015;Díaz-Lee et al, 2011). The variations in the frequencies observed between the studies may be associated with age, sample size, management practices, study design or different diagnostic techniques (Hatam-Nahavandi et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…The rate of occurrence of cryptosporidiosis is usually higher in dairy cattle due to the intensive rearing system, which favors contact between animals and increases transmission of the parasite (Martins-Vieira et al, 2009). In Brazil, its prevalence ranges from 3% to 64% (Feitosa et al, 2004;Oliveira et al, 2007;Sevá et al, 2010;Meireles et al, 2011;Silva et al, 2011;Lima et al, 2013;Silva et al, 2013;Coelho et al, 2016;Toledo et al, 2017;Holsback et al,-2018;Cruvinel et al, 2020). Most of these studies were conducted in states where herds are mainly composed of dairy cattle, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Older lambs demonstrate delayed growth, and adults are generally refractory to infection and illness (XIAO et al, 1993), but can eliminate oocysts in the feces, thereby contaminating the environment (MAJEWSKA et al, 2000;ZUCATTO et al, 2015). In Brazil, studies on cryptosporidiosis in ruminants have primarily been performed in the Southeast, mainly in the states of Rio de Janeiro (COSENDEY et al, 2008;FIUZA et al, 2011), Minas Gerais (GARCIA & LIMA, 1993;GARCIA & LIMA, 1994;LIMA et al, 2013), andSão Paulo (AQUINO et al, 2015;COELHO et al, 2016;FEITOSA et al, 2004;FÉRES et al, 2009;PAZ E SILVA et al, 2013SEVÁ et al, 2010;SILVA-JUNIOR et al, 2011). In the state of Paraná, infection with Cryptosporidium was evaluated in captive birds (NAKAMURA et al, 2009), dogs with diarrhea (NAVARRO et al, 1997), horses (FUJII et al, 2014, wild birds and mammals (SNAK et al, 2015), cattle (TOLEDO et al, 2017 and sheep (SNAK et al, 2017).…”
Section: Introductionmentioning
confidence: 99%